PENGELOLAAN KEUANGAN BAGI USAHA MIKRO KECIL MENENGAH (UMKM) DI KELURAHAN PURWOKERTO UTARA KECAMATAN BATURRADEN KABUPATEN BANYUMAS - Triani Arofah; Umi Pratiwi; Agus Sunarmo (Jurnal Pengabdian Bisnis dan Akuntansi Soedirman (JPBA), 2022)
Purwokerto Utara village has a lot of UMKM which has been running for a long time. Some problems found in the understanding and efforts that need to be done in improving their business, especially micro and small business, which causes less development of micro and small enterprises in Purwokerto Utara urban areas, among others, the lack of understanding about accounting. The perpetrators of UMKM generally only do a simple record of income and expenditures. Some even do not record the rent as a business expense, so the business is seen to generate a large profit because the burden is not recorded properly. The result is that the listing does not describe the actual financial condition of the business. The problem faced by partners is the absence of training on business financial management directly. Solutions needed for the problem is the provision of training for UMKM in terms of managing finances by using accounting. The outcome of this solution is the ability of partners to use accounting easily to improve the financial performance of their business. The outcome of this solution in the form of partner knowledge about the management of good business finances and other true outcomes is scientific articles published at the local level. The result of the recapitulation of questionnaires distributed to the participants explained that community service is very beneficial because it increases participats’ knowledge about financial management for UMKM.